Environmental Pollution and Asthma - Croce, Miguel (1997)
Between 10,000 and 20,000 liters of air are movilized by human beings everyday. This procces is altered by pollution, and are associated with a greater incidence of rhinoconjunctivitis, asthma and bronchitis. We review the main pollution sources in the domestic environment, both biological and unbiological; as wen its pathogenic mechanism's and the engagement between ponution amid respiratory diseases, mainly asthma. Finany, we show the proposed mechanisms involved with this association.